Synthesis of Zn-based 1D and 2D coordination polymer nanoparticles in block copolymer micelles. Issue 10 (14th September 2020) - Göbel, Christoph; Hörner, Gerald; Greiner, Andreas; Schmalz, Holger; Weber, Birgit
Abstract : Synthesis of 2D coordination network nanoparticles using block copolymer micelles as template. Abstract : Nanoparticles of the 1D and 2D coordination polymers [Zn(OAc)2 (bipy)] n and [Zn(TFA)2 (bppa)2 ] n were prepared, employing polystyrene- block -poly(4-vinylpyridine) diblock copolymers with different weight fractions of the 4-vinylpyridine (4VP) block and comparable overall molecular weights of M n ≈ 155 kg mol −1 as template (SV-15 and SV-42 with 15 and 42 wt% 4VP, respectively). [Zn(OAc)2 (bipy)] n nanoparticles were successfully synthesised within the 4VP core of SV-42 micelles, showing a core size of D core = 47 ± 5 nm and a hydrodynamic diameter of D h = 157 ± 46 nm, determined by transmission electron microscopy (TEM) and dynamic light scattering (DLS). The crystallinity of the composite is quite low, showing only low intensity reflexes in the powder X-ray diffraction (PXRD) pattern with the highest particle load. No indications for larger microcrystals were detected by scanning electron microscopy (SEM), proving the successful integration of the coordination polymer nanoparticles within the micellar cores. Nanocomposites of the 2D coordination network [Zn(TFA)2 (bppa)2 ] n were synthesised using both diblock copolymers. The particle core sizes (from TEM) and hydrodynamic diameters (from DLS) correlate with the 4VP fraction of the micelles, resulting in D core = 46 ± 6 nm for SV-42 and 15 ± 2 nm for SV-15 and D h = 340 ± 153 nm and 177 ± 57 nm, respectively. The successful synthesis was proven by PXRD and SEM images, confirming the absence of larger crystallites. Hence, it is possible to synthesise nanocomposites of Zn-based 1D and 2D coordination polymers by a direct approach utilizing diblock copolymer micelles as template.